2016
DOI: 10.7860/jcdr/2016/21335.8613
|View full text |Cite
|
Sign up to set email alerts
|

Bellini Duct Carcinoma: A Rare Entity

Abstract: Bellini duct carcinoma of kidney derives from collecting duct and is associated with an aggressive course and extremely poor prognosis. Here, we report an interesting case of Collecting Duct Carcinoma (CDC) with Inferior Vena Cava (IVC) thrombus and large retroperitoneal lymph nodes and diffuse desmoplastic reaction. The patient underwent left open radical nephrectomy with IVC thrombectomy and regional lymphadenectomy. Based on morphological and immunohistochemical analysis, diagnosis of collecting duct (Belli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 7 publications
1
12
0
9
Order By: Relevance
“…Till 2013, almost 200 cases have been reported in the literature [5] with less than 5 cases reported later [1,5]. An increased prevalence of BDC was reported in patients with renal failure and nephrolithiasis and on hemodialysis [6], aligning well with our patient's history of recurrent urinary stones.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Till 2013, almost 200 cases have been reported in the literature [5] with less than 5 cases reported later [1,5]. An increased prevalence of BDC was reported in patients with renal failure and nephrolithiasis and on hemodialysis [6], aligning well with our patient's history of recurrent urinary stones.…”
Section: Discussionsupporting
confidence: 84%
“…This fact should always be kept in mind since it contributed to our initial misdiagnosis; our patient mostly presented nonspecific symptoms. The rest may be atypical (acute renal failure, metastatic lesions to bones or meninges, and lymphadenopathy) [5][6][7]. Common metastasis sites include the lungs, bones (as osteoblastic lesions), liver, and adrenal glands [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…CDC is defined as a malignant epithelial tumor arising from the lining cells of the collecting ducts of Bellini in the renal medulla. This is different from most RCCs, which occur due to malignant proliferation of the proximal tubular of nephron cells, and from urothelial carcinoma (UC) which arises from the transitional epithelium lining of the mucosa of the bladder, renal pelvis and ureters (Mishra, Manikandan, Dorairajan, Mittal, & Rekha, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Pepek and colleagues found that the incidence rate was only 1-2% of all renal tumors, generally affected people ages 13-83 years with an average age of 55 years. The male to female incidence ratio is 2:1 and found mostly in white patients, African-American, and some other races (Seo, Yoon, & Ro, 2017;Harbin et al, 2015;Mishra et al, 2016). ABSTRACT Traumatic severe brain injury is a fatal injury, with a mortality rate of up to 50%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation